2017
DOI: 10.1021/acs.macromol.7b01276
|View full text |Cite
|
Sign up to set email alerts
|

Rigid Hyperbranched Polycarbonate Polyols from CO2 and Cyclohexene-Based Epoxides

Abstract: Hyperbranched, multifunctional polycarbonate polyols based on CO2, cyclohexene oxide (CHO), and the “inimer” (initiator–monomer) (4-hydroxymethyl)­cyclohexene oxide (HCHO) were prepared in one-pot syntheses. The related linear poly­(hydroxymethyl cyclohexene carbonate) structures based on protected HCHO and postpolymerization deprotection were also synthesized as model compounds. The content of hydroxyl functionalities was adjustable for both linear and hyperbranched terpolymer systems. All CO2/epoxide polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 65 publications
2
30
0
Order By: Relevance
“…Polyethers are important industrial polymers where they are used in the production polyurethanes , and are found in common consumer products such as laxatives, eye drops, medicines, and lubricants, as well as in the technological applications such as lithium-ion batteries, separation membranes, , antifouling coatings, , and biomedical applications . The ubiquity and utility of polyether materials are the results of their functional monomer precursors, epoxides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyethers are important industrial polymers where they are used in the production polyurethanes , and are found in common consumer products such as laxatives, eye drops, medicines, and lubricants, as well as in the technological applications such as lithium-ion batteries, separation membranes, , antifouling coatings, , and biomedical applications . The ubiquity and utility of polyether materials are the results of their functional monomer precursors, epoxides.…”
Section: Introductionmentioning
confidence: 99%
“…Thio-aluminum initiators (SAls) can be easily synthesized from the reaction of a thiol-containing ligand and trimethylaluminum. The kinetic and molecular weight control of epoxide polymerizations initiated by SAls was investigated by tuning the catalyst concentration and monomer to initiator ratio and characterized by 1 H NMR spectroscopy and size-exclusion chromatography (SEC). Initiator chemistry was varied to investigate polymer end group control as well as the effect on polymerization kinetics.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The increase in T g is attributed to inter-/intra-chain hydrogen bonding, a phenomenon which is common in biopolymers and has been observed for other hydroxyl-functionalized polymers. 62,63 The entire series of alternating functionalized polymers (P1(b)-P1(f)) show lower T g values (À8 C to 86 C) than P1(a) probably due to the increased hydrodynamic volumes (Fig. S28 †).…”
Section: Resultsmentioning
confidence: 99%
“…Adjustable T g s between 72 and 105 °C and low intrinsic viscosities down to 5.69 cm 3 g −1 in DMF were obtained for the hyperbranched structures. The linear analogues showed T g values between 113 and 141 °C …”
Section: Variation Of the Polymer Architecturementioning
confidence: 99%